3D kinematics of the interphalangeal joints in the forelimb of walking and trotting horses - Clayton, H. M.; Sha, D. H.; Stick, J. A.; Robinson, P. (Veterinary and Comparative Orthopaedics and Traumatology, 2007)
The objective was to measure 3D rotations of the distal (DIP) and proximal (PIP) interphalangeal joints at walk and trot. 3D trajectories of markers fixed to the proximal phalanx, middle phalanx and the hoof wall of the right forelimb of four sound horses were recorded at 120 Hz. Joint kinematics were calculated in terms of anatomically-based joint coordinate systems between the bone segments. Ranges of motion were similar at walk and trot. Values for the DIP joint were: flexion/extension: 46 ± 3° at walk, 47 ± 4° at trot; internal/ external rotation: 5 ± 1° at walk, 6 ± 3° at trot; and adduction/abduction: 5 ± 2° at walk, 5 ± 3° at trot. Within each gait, kinematic profiles at the DIP joint were similar between horses with the exception of adduction/abduction during breakover, which may vary depending on the direction of hoof rotation over the toe. Knowledge of the types and amounts of motion at the DIP joint will be useful in understanding the aetiology and treatment of injuries to the soft tissues, which are being recognized more frequently through the use of sensitive imaging techniques. Ranges of motion for the PIP joint were: flexion/extension: 13 ± 4° at walk, 14 ± 4° at trot; adduction/abduction: 3 ± 1° at walk, 3 ± 1° at trot; and internal/external rotation: 3 ± 1° at walk, 4 ± 1° at trot. The PIP joint made a significant contribution to flexion/extension of the digit. During surgical arthrodesis, the angle of fusion may be important since loss of PIP joint extension in late stance is likely to be accommodated by increased extension of the DIP joint.
Keywords: Kinematics; joint angles; coffin joint; pastern joint; horse